Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Melalui Keterikatan Karyawan Sebagai Variabel Mediasi Pada Pt. Duren Mandiri Fortuna Jambi - Cucu Hayati (Nomico, 2024)
This study aims to determine the effect of transformational leadership on employee performance with employee engagement as a mediating variable. Research conducted using quantitative methods by distributing questionnaires to respondents. The population and sample for this study were employees of PT Duren Mandiri Fortuna with a total sampling of 72 people. The data analysis method used is descriptive statistical analysis with SEM-PLS techniques in the SmartPLS program (v.3.2.9). The results of this study reveal that there is a positive and significant relationship from transformational leadership to employee performance, transformational leadership has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on employee performance and employee engagement is able to mediate between transformational leadership and employee performance at PT Duren Mandiri Fortuna Jambi. Therefore, it is recommended that the leader of PT Duren Mandiri Fortuna Jambi be able to create comfort during discussions with employees and provide inspiration so that employees are more creative, keep monitoring employee work progress so that time management is well created, and show enthusiastic support for employees so that employees feel their role has contributed to the progress of PT Duren Mandiri Fortuna Jambi.